OSM-9 and an amiloride-sensitive channel, but not PKD-2, are involved in mechanosensation in C. elegans male ray neurons - Hu Zhang (Nature Portfolio, 2018)
Abstract Mechanotransduction is crucial for touch sensation, hearing, proprioception, and pain sensing. In C. elegans, male ray neurons have been implicated to be involved in the mechanosensation required for mating behavior. However, whether ray neurons directly sense mechanical stimulation is not yet known, and the underlying molecular mechanisms have not been identified. Using in vivo calcium imaging, we recorded the touch-induced calcium responses in male ray neurons. Our data demonstrated that ray neurons are sensitive to mechanical stimulation in a neurotransmitter-independent manner. PKD-2, a putative sensor component for both mechanosensation and chemosensation in male-specific neurons, was not required for the touch-induced calcium responses in RnB neurons, whereas the TRPV channel OSM-9 shaped the kinetics of the responses. We further showed that RnB-neuron mechanosensation is likely mediated by an amiloride-sensitive DEG/ENaC channel. These observations lay a foundation for better understanding the molecular mechanisms of mechanosensation.